A study on the agriculture, forestry and natural resources (AFNR) programs in UPLB with focus on BS Agriculture, 1988-2010 - Lalican, Nelita M. (2011)
Enrollment in AFNR programs in 2002-2003 wig a total of 4,682 students, thereafter, a decreasing trend was observed especially in agricultural chemistry, veterinary medicine, forestry, forest ranger and agribusiness. Agriculture maintained its top portion in terms of enrollees during the ten-year period 1998-2007 with the highest enrollment in 2001-2002. Promising AFNR programs included development communication, food technology and agricultural economics which showed positive change in enrollment of 37.58%, 8.08% and 4.08%, respectively. The enrollment in agricultural engineering was almost consistent. Agriculture was leading in terms of number of graduates followed by development communication, forestry, food technology and agribusiness. There was 145% increase in the graduates of agricultural engineering in 2007-2008. In 2000 and 2001, the new freshmen in the UPLB-BSA program were mostly qualifiers and non-qualifiers but in 2010 the proportion gecame favorable to the waitlisted students. On the average, the graduates in 1988-1996 were enrolled for 10.59 semester to finish the BS Agriculture. A large number of the BSA graduates were children of unemployed parent but scholarships and STFAP helped them sustain their studies until graduation. They chose UPLB because of its reputation as an excellent academic institution. Parents or relatives had greatly flue cede the graduates in taking up BS Agriculture. Some of the graduate have been pursuing graduates studies. They were very satisfied with the knowledge/skills acquired for. He BSA program, and they consider them effective in influencing their lives. The level of influence is more than the satisfaction they gained from the program. The employer of the BSA graduates rated them high in knowledge on the major fields of study, specific technical knowledge required for the job, customer relations,creasing comprehension, written communication, use of computer and equipment or technology specific for getting job, leadership, advance computer literacy and negotiation skills. The BSA graduates were much better in the management of organizational resources, project management and in negotiation compared to other UPLB-AFNR graduates. The employers considered these skills highly important to them. The graduates need enhancement in their ability to set goals and translate theory to practice, verbal communication, teamwork, critical thinking and comprehension of information that are connected to the job. They should also cultivate their empathy of understanding o the feelings and motives of others.
Keywords: Agricultural education -- University of the Philippines (Los Baños). College of Agriculture